Level of knowledge towards virtual learning among clinical officer students at Mildmay Institute of Health Sciences in Wakiso district. A cross-sectional study. - Namayega, Patricia Mary; Okwany, Jimmy; Naggulu, Immaculate Prosperia; Nansereko, Hasifa; Ssemuwemba, Francisco; Nalubega, Jane Frank (Student's Journal of Health Research Africa, 2026)
Background: The level of knowledge towards virtual learning refers to students’ understanding and awareness of e-learning platforms, digital tools, and their academic use in online education. This study aims to determine the Level of knowledge towards virtual learning among clinical officer students at Mildmay Institute of Health Sciences in Wakiso district. Methodology: A descriptive cross-sectional study with a quantitative approach was conducted among 75 randomly selected clinical officer students from Year 3.1, Year 2.1, and Year 3.2. Data were collected using electronic questionnaires distributed to students to capture information on their knowledge related to virtual learning. Analysis was done using Microsoft Excel, and results were presented in frequency distribution tables, bar graphs, and pie charts. Results: The majority of the participants were female students (66.7%), and male students were 33.3%. Most participants were aged 25–29 years (65.3%), followed by those aged 20–24 years (32.0%), with a small proportion aged 30 years and above (2.7%). 57 (76%) found their devices reliable for attending virtual learning classes regularly, whereas 18(24%) found them unreliable. 60(80%) reported that they were aware of virtual learning platforms and tools, and 15(20%) reported that they were not aware of them. 58(96.7%) reported having ever used any of the platforms for academic purposes, whereas 2(3.3%) reported having never. 69(92%) had ever used medical applications on their phones for learning purposes, whereas 6(8%) had never used the medical applications on their phones for learning purposes. Knowledge gaps included limited access to e-learning tools, low awareness, and inadequate prior experience. Conclusions: Students showed moderate knowledge of virtual learning, being aware of platforms and using medical apps, but most had no prior experience before joining the institute. Recommendations: Provide orientation, digital skills training, and guided practice to enhance students’ competence and confidence in virtual learning.